1982
DOI: 10.1161/01.cir.65.1.202
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective interaction of sulfinpyrazone with racemic warfarin and its separated enantiomorphs in man.

Abstract: SUMMARY Although serious hemorrhage during therapeutic coadministration of sulfinpyrazone and racemic warfarin occurs, no prospective studies have been done. In this study, single oral doses of racemic warfarin, 1.5 mg/kg, were administered to six normal subjects with and without oral sulfinpyrazone, 400 mg daily. Both the hypoprothrombinemia (p < 0.001) and the plasma warfarin concentrations (p < 0.05) were significantly augmented. To determine if this interaction was stereoselective, the experiments were rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

1982
1982
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 17 publications
0
14
1
Order By: Relevance
“…The increase in AUC and plasma half-life and the decrease in plasma clearance indicate that there is inhibition of metabolism of the R enantiomer but no consistent change in the metabolism of S warfarin. In contrast, previous studies on the stereoselective nature of warfarin drug interactions O'Reilly, 1976O'Reilly, , 1980O'Reilly, , 1982 have shown an increase in the mean plasma half-life of S warfarin due to decreased clearance. The mean plasma half-life of the R enantiomer however has been shown to decrease (phenylbutazone and sulphinpyrazone) or remain unchanged (metronidazole and cotrimoxazole).…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…The increase in AUC and plasma half-life and the decrease in plasma clearance indicate that there is inhibition of metabolism of the R enantiomer but no consistent change in the metabolism of S warfarin. In contrast, previous studies on the stereoselective nature of warfarin drug interactions O'Reilly, 1976O'Reilly, , 1980O'Reilly, , 1982 have shown an increase in the mean plasma half-life of S warfarin due to decreased clearance. The mean plasma half-life of the R enantiomer however has been shown to decrease (phenylbutazone and sulphinpyrazone) or remain unchanged (metronidazole and cotrimoxazole).…”
Section: Discussioncontrasting
confidence: 69%
“…(,ug ml' h) (h) (ml h-' kg') (1 kg') (,sg ml' h) (h) (ml h-' kg-') (I kg-') The results show a stereoselective pharmacokinetic interaction between cimetidine and the R enantiomer of warfarin. R warfarin is less potent than S warfarin O'Reilly, 1974;Wingard et al, 1978 O'Reilly, 1976O'Reilly, , 1980O'Reilly, , 1982 have shown an increase in the mean plasma half-life of S warfarin due to decreased clearance. The mean plasma half-life of the R enantiomer however has been shown to decrease (phenylbutazone and sulphinpyrazone) or remain unchanged (metronidazole and cotrimoxazole).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a CYP2C9 inhibitor, equipotent to phenylbutazone and sulfinpyrazone. [5][6][7] Therefore, it is suggested that when LOS and CYP2C9 inhibitors are given concomitantly, the bioavailability of E3174 is decreased; leading theoretically to decreases the pharmacodynamic effects of LOS. In this study, to evaluate the potential drug interaction between LOS and CYP2C9 inhibitors, the effects of BUC on the pharmacokinetics of LOS and E3174 were studied in healthy human volunteers and rats.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, for warfarin it was shown in man that other drugs can affect the metabolism of the enantiomers in a qualitative and quanti-tative different manner. Such stereoselective biotransformation interactions with the warfa rin enantiomers have been demonstrated, e.g., for phenylbutazone (Lewis et ai, 1974), metro nidazole (O'Reilly, 1976), and co-trimoxazole (O'Reilly, 1977) but not for phénobarbital (Breckenridge and Orme, 1976). These findings lead to the suggestion that interactions of cer tain drugs with warfarin could be minimized by treating patients with one of the enantiomers instead of racemic drug (O ' Reilly, 1976;.…”
Section: Introductionmentioning
confidence: 99%